Evidence of tuned anharmonicity in the thermoelectric material Cu2-x S - Seungyub Song; Takashi Saito; Sanghyun Lee; Masato Hagihala; Yoshihisa Ishikawa; Shuki Torii; Kazuhiro Mori; Shinichi Itoh; Kug-Seung Lee; Deok-Yong Cho; Takashi Kamiyama (Communications Materials)
Abstract The mechanisms underlying the low thermal conductivity of Cu2-x (S, Se) have been attracting considerable attention. However, Cu defects in Cu2-x (S, Se) have been reported to lead to an unusual increase in lattice thermal conductivity, unlike the typical decrease caused by phonon scattering induced by point defects. We propose that this anomaly is caused by atomic anharmonicity. Here, we perform neutron diffraction on Cu defect-controlled Cu2-x S to reveal that as Cu defects increase, the volume of tetrahedral Cu distribution significantly shrinks and centralizes, suggesting a change in the potential around the Cu atom. We find that the degree of anharmonicity is highest in Cu2S and decreases with increasing Cu defects using one-particle potential fitting. This trend explains the increase in lattice thermal conductivity with increasing Cu defects. Our findings show that anharmonicity can be tuned through Cu defects, explaining the underlying mechanism of the anomalous increase in the lattice thermal conductivity.